A “moral state” or a new theocracy after all? Polemical notes in connection with the new concept of Russian statehood - Z. A. Stankevich (Правоприменение, 2021)
The article contains a review of Sergey N. Baburin's monograph “The Moral State. The Rus-sian view on the values of constitutionalism”. The review is presented in the form of a po-lemic about the concept of the so-called moral state, which has recently gained some pop-ularity in Russia due to the strengthening of conservative-traditionalist principles in the country's domestic and foreign policy.